2000
DOI: 10.1007/s001140050699
|View full text |Cite
|
Sign up to set email alerts
|

Indian-Asian Relationship: mtDNA Reveals More

Abstract: Recent studies on human mtDNA have identified continent-specific restriction enzyme sites and resultant haplo-groups among populations from different regions of the world. Such studies have helped in elaborating the models for human migrations. We have studied Indian mtDNAs to identify the recognized world ethnic elements present in it. The results presented here are based on the study of DdeI 10394 site along with the associated Asian-specific AluI 10397 site in the mtDNA sequences of the Indian samples. On e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Very high frequency of haplogroup M in both these tribes could be due to their small size. Overall, in this study, about 63 per cent of the individuals possessed haplogroup M. This is consistent with the earlier published data (Anderson et al 1981;Passarino et al 1996;Barnabas et al 2000;Roychoudhury et al 2000;Edwin et al 2002;Basu et al 2003). The in situ evolved populations have frequencies comparable with the ancient ethnic groups.…”
Section: Haplogroup M and Nsupporting
confidence: 94%
“…Very high frequency of haplogroup M in both these tribes could be due to their small size. Overall, in this study, about 63 per cent of the individuals possessed haplogroup M. This is consistent with the earlier published data (Anderson et al 1981;Passarino et al 1996;Barnabas et al 2000;Roychoudhury et al 2000;Edwin et al 2002;Basu et al 2003). The in situ evolved populations have frequencies comparable with the ancient ethnic groups.…”
Section: Haplogroup M and Nsupporting
confidence: 94%
“…Earlier studies (Barnabas et al 2000;Clark et al 2000;Watkins et al 1999) have also indicated that this 9-bp deletion is extremely infrequent in India. As observed by us earlier (Roychoudhury et al 2000), there is extensive sharing of haplotypes across ethnic groups; one haplotype (00111101010) was modal across all the populations.…”
Section: Figmentioning
confidence: 88%
“…The DNA samples analysed by Quintana-Murci et al (2001) did not include any specific ethnic population of India; it is unclear whether any tribal samples from India were included. Similarly, the studies by Barnabas et al (1996Barnabas et al ( , 2000 were also on samples of mixed ethnicity.…”
Section: Introductionmentioning
confidence: 97%
“…Over past two decades, allogenic BMT has become the treatment of choice for patients suffering from malignant hematological disorders [acute myeloid leukemia (AML), chronic myeloid leukemia (CML) and acute lymphoblastic leukemia (ALL)], severe cytopenias [myelodysplastic syndrome (MDS) and severe aplastic anemia (AA)] and other non-malignant hematological disorders (a-and b-thalassemia, severe combined immunodeficiency, haemoglobinopathies), etc. [5][6][7][8][9][10][11][12][13][14] Allogenic BMT has been effective in reconstitution of normal haemopoiesis in these patients. The success of this treatment modality is mainly affected by the recurrence of the underlying disease.…”
Section: Introductionmentioning
confidence: 99%
“…This element of uniqueness is employed for various purposes including forensic applications and other molecular tests, which are of clinical relevance. [7][8][9][10][11][12][13][14] One of the utility is in evaluating chimerism in allogenic BMT, which is an important state which develop after engraftment. On the basis of chimerism we can know about the disease relapse, graft rejection or GVHD.…”
Section: Introductionmentioning
confidence: 99%